Most valuable stakeholders: The impact of employee orientation on corporate financial performance - De Bussy, Nigel; Suprawan, L. (Elsevier, 2012)
In sports, the Most Valuable Player award goes to the individual or group of players who have contributed most to the success of the team. This paper presents the results of two Australian empirical studies conducted six years apart, which suggest that, in business, employees are the most valuable stakeholder group. In particular, we find evidence to support the proposition that employee orientation contributes more to corporate financial performance (CFP) than orientation towards any other individual primary stakeholder group, including customers, communities, suppliers and shareholders. These findings have practical implications for corporate level strategy and the prioritization of budgetary resources by communication managers. From a theoretical perspective, the paper contributes to the debate on the best way to conceptualize employee orientation.